2022
DOI: 10.3390/ijerph19138131
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Perception of the Palestinian Health Workforce Accreditation and Regulation System: A Focus on Conceptualization, Influencing Factors and Barriers, and the Way Forward

Abstract: The Health Workforce Accreditation and Regulation (HWAR) is a key function of the health system and is the subject of increasing global attention. This study provides an assessment of the factors affecting the Palestinian HWAR system, identifies existing gaps and offers actionable improvement solutions. Data were collected during October and November 2019 in twenty-two semi-structured in-depth interviews conducted with experts, academics, leaders, and policymakers purposely selected from government, academia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The healthcare providers, on the other hand, demonstrated that the main obstacles preventing the hospital from fully benefiting from the CBAHI accreditation were distributed as follows: inefficient IT tools, a lack of time, a lack of support from the top administration, a lack of communication at the hospital/ward, a lack of support from the administration department, and a lack of relevance for daily tasks. Previous research has shown that the claimed worker shortage and hiring difficulties [34], infrastructure gaps, low levels of physician engagement [24], limited financial support [35], and bureaucratic decisionmaking procedures [36] represent barriers to accreditation standards implementation [37]. Further future studies are required to confirm these findings on a larger scale and eliminate selection bias.…”
Section: Discussionmentioning
confidence: 95%
“…The healthcare providers, on the other hand, demonstrated that the main obstacles preventing the hospital from fully benefiting from the CBAHI accreditation were distributed as follows: inefficient IT tools, a lack of time, a lack of support from the top administration, a lack of communication at the hospital/ward, a lack of support from the administration department, and a lack of relevance for daily tasks. Previous research has shown that the claimed worker shortage and hiring difficulties [34], infrastructure gaps, low levels of physician engagement [24], limited financial support [35], and bureaucratic decisionmaking procedures [36] represent barriers to accreditation standards implementation [37]. Further future studies are required to confirm these findings on a larger scale and eliminate selection bias.…”
Section: Discussionmentioning
confidence: 95%
“…Pengaruh insentif terhadap tenaga kesehatan terhadap proses akreditasi puskesmas memiliki implikasi yang penting dalam meningkatkan kualitas layanan kesehatan di level primer (26). Insentif yang diberikan kepada tenaga kesehatan, baik dalam bentuk finansial maupun non-finansial, dapat menjadi pendorong utama bagi mereka untuk meningkatkan kinerja dan komitmen mereka terhadap standar-standar akreditasi yang ditetapkan.…”
Section: Pengaruh Insentif Tenaga Kesehatan Terhadap Akreditasi Puske...unclassified
“…Berdasarkan beberapa penelitian, Puskesmas dengan tenaga kesehatan yang memiliki masa kerja campuran yakni gabungan antara yang baru dan yang lama cenderung lebih berhasil dalam memenuhi standar akreditasi. Tenaga kesehatan yang lebih muda seringkali membawa energi baru dan keakraban dengan teknologi terkini, sedangkan mereka yang lebih berpengalaman memberikan pengetahuan mendalam tentang praktik medis dan pelayanan pasien (23,26,39). Masa kerja tenaga kesehatan memiliki pengaruh signifikan terhadap proses dan hasil akreditasi Puskesmas.…”
Section: Pengaruh Masa Kerja Tenaga Kesehatan Terhadap Akreditasi Pus...unclassified